Syncretic Dynamics Of The Relationship Between Religious Teachings And Traditional Values In The Marsodip Tradition Of The Pak Pak Tribe Of Sitellu Tali Urang Jehe Kab. Pak Pak Bharat - Capah, Hidayatul Fahmi; ., Irwansyah (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2025)
This research aims to analyze the syncretic dynamics between religious teachings and customary values in the Marsodip tradition, a cultural heritage of the Pak Pak ethnic community in Sitellu Tali Urang Jehe Subdistrict, Pak Pak Bharat Regency. The Marsodip tradition reflects the community’s effort to preserve cultural identity amid the challenges of modernization and shifting religious values. Using a qualitative approach and ethnographic method, data were collected through participant observation and in-depth interviews with 3 key informants, including traditional leaders, religious figures, and community members involved in the tradition. The findings reveal a strong form of syncretism, where customary and religious values do not negate one another but engage in a dynamic interaction through processes of adaptation and negotiation. The syncretic strategies developed by the community include symbolic modifications in rituals, reinterpretation of customary values through religious perspectives, and the involvement of religious leaders in the implementation of traditions. This study shows that Marsodip serves not only as cultural preservation but also as a space for active dialogue between tradition and religion in the context of social change. The research contributes to the discourse on cultural and religious syncretism in traditional Indonesian societies